2021
DOI: 10.9734/ajob/2021/v12i430168
|View full text |Cite
|
Sign up to set email alerts
|

Concomitancy of Entomophilous and Soil Transmitted Nematodes in Selected Insects

Abstract: Aim: To determine the occurrence of entomophilous and soil transmitted nematodes of three insect species; Zonocerus variegatus, Gryllotalpa orientalis and Mantis religiosa in Obio Akpor, Local Government Area of Rivers State, Nigeria. Methodology: The insect samples were collected with entomological sweep net as described by Colwell [1] and pitfall traps as described by Davies [2]. Insect samples were dissected using Stubbins’ method [3] while nematodes in the insects were isolated and identified accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Previous studies have reported that the abundance of specific insects boosts the rate of EPN infectivity (Demarta et al, 2014;Campos-Herrera, 2015). Ozeum et al (2021) isolated 148…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have reported that the abundance of specific insects boosts the rate of EPN infectivity (Demarta et al, 2014;Campos-Herrera, 2015). Ozeum et al (2021) isolated 148…”
Section: Discussionmentioning
confidence: 99%
“…Following (Ozeum et al ., 2021), the weight (g) of the insect samples was weighed using an electronic measuring scale, while a meter rule was used to measure the standard and total lengths (cm) of the insects. The standard length of the samples involves the length of the insect, excluding the jumping legs, while the total length includes the stretched-out jumping legs of the insects.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations